2019
DOI: 10.1007/978-3-030-31517-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Greenify: A Game with the Purpose of Test Data Generation for Unit Testing

Abstract: One of the most important, but tedious and costly tasks of software testing process is test data generation. Several methods for automating this task have been presented, yet due to their practical drawbacks, test data generation is still widely performed by humans in industry.In our previous work, we employed the notion of Game With A Purpose (GWAP) and introduced Rings as a GWAP to reduce time and costs of human-based test data generation and increase its appeal to engage even nontechnical people. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Rings and Greenify were early works employing GWAP in human-based test data generation with promising results [9,10]. However, they had certain problems, including limitations on the number of program inputs, scalability, etc.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rings and Greenify were early works employing GWAP in human-based test data generation with promising results [9,10]. However, they had certain problems, including limitations on the number of program inputs, scalability, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The players should change the values of the sliders and checkboxes until the color of all connected bubbles turns green. The results indicated that Greenify outperformed Rings, the conventional human-based approach, and the random test data generation method in terms of path coverage percentage and elapsed time for generating test data [10]. However, Greenify could not solve the following challenges of Rings:…”
Section: Related Workmentioning
confidence: 96%
See 3 more Smart Citations